Informação e desinformação em tempos de pós-verdade: um estudo a respeito da propagação de notícias falsas nas mídias sociais - Nascimento, Lucia Cristina Oliveira (2022)
The present research proposes to discuss, conceptually and historically, regarding the post-truth problem. In addition, it intends to draw a brief overview of the themes that are related to the subject of study, such as: Information Technology, Social Media, Fake News, Bullshit and Desinformation in contemporary society. National and international authors guide the exercise of referential research in this study, in order to bring a plurality of views about the subject of study. The field research was carried out to identify how a sample of undergraduate and postgraduate at the Federal University of Rio de Janeiro understand the phenomenon called "Post-truth" and also as how they perceive, deal with, believe and propagate desinformation and false news received through social media. The qualitative approach was used, the method adopted was the application of an online questionnaire and the data processing was qualitative and quantitative, inspired by the Collective Subject Discourse. It is noticed, through the speech of the research subjects, that these are aware that nowadays disinformation has been widely propagated through social media and affects different aspects of society. Therefore, these individuals look for strategies to verify the contents received through these digital platforms in order to prevent the spread of fake news.